Skeletal interoception and prospective application in biomaterials for bone regeneration - Long Bai; Jilong Li; Guangfeng Li; Dongyang Zhou; Jiacan Su; Changsheng Liu (Bone Research)
Abstract Accumulating research has shed light on the significance of skeletal interoception, in maintaining physiological and metabolic homeostasis related to bone health. This review provides a comprehensive analysis of how skeletal interoception influences bone homeostasis, delving into the complex interplay between the nervous system and skeletal system. One key focus of the review is the role of various factors such as prostaglandin E2 (PGE2) in skeletal health via skeletal interoception. It explores how nerves innervating the bone tissue communicate with the central nervous system to regulate bone remodeling, a process critical for maintaining bone strength and integrity. Additionally, the review highlights the advancements in biomaterials designed to utilize skeletal interoception for enhancing bone regeneration and treatment of bone disorders. These biomaterials, tailored to interact with the body’s interoceptive pathways, are positioned at the forefront of innovative treatments for conditions like osteoporosis and fractures. They represent a convergence of bioengineering, neuroscience, and orthopedics, aiming to create more efficient and targeted therapies for bone-related disorders. In conclusion, the review underscores the importance of skeletal interoception in physiological regulation and its potential in developing more effective therapies for bone regeneration. It emphasizes the need for further research to fully understand the mechanisms of skeletal interoception and to harness its therapeutic potential fully.